Papain-Like Cysteine Protease Gene Family in Fig (Ficus carica L.): Genome-Wide Analysis and Expression Patterns - Zhai, Yanlei; Cui, Yuanyuan; Song, Miaoyu; Vainstein, Alexander; Chen, Shangwu; Ma, Huiqin (Frontiers in Plant Science, 2021)
The papain-like cysteine proteases (PLCPs) are the most abundant family of cysteine proteases in plants, with essential roles in biotic/abiotic stress responses, growth and senescence. Papain, bromelain and ficin are widely used in food, medicine and other industries. In this study, 31 PLCP genes (FcPCLPs) were identified in the fig (Ficus carica L.) genome by HMM search and manual screening, and assigned to one of nine subfamilies based on gene structure and conserved motifs. SAG12 and RD21 were the largest subfamilies with 10 and 7 members, respectively. The FcPCLPs ranged from 1128 bp to 5075 bp in length, containing 1–10 introns, and the coding sequence ranged from 624 bp to 1518 bp, encoding 207–505 amino acids. Subcellular localization analysis indicated that 24, 2 and 5 PLCP proteins were targeted to the lysosome/vacuole, cytoplasm and extracellular matrix, respectively. Promoter (2000 bp upstream) analysis of FcPLCPs revealed a high number of plant hormone and low temperature response elements. RNA-seq revealed differential expression of 17 FcPLCPs in the inflorescence and receptacle, and RD21 subfamily members were the major PLCPs expressed in the fruit. Sixteen and five FcPLCPs responded significantly to ethylene and light, respectively. Proteome analyses revealed 18 and 5 PLCPs in the fruit cell soluble proteome and fruit latex, respectively. Ficins were the major PLCP in fig fruit, with decreased abundance in inflorescences, but increased abundance in receptacles of commercial-ripe fruit. FcRD21B/C and FcALP1 were aligned as the genes encoding the main ficin isoforms. Our study provides valuable multi-omics information on the FcPLCP family and lays the foundation for further functional studies.